COPD and cancer mortality: the influence of statins. Issue 11 (30th August 2009) - van Gestel, Y R B M; Hoeks, S E; Sin, D D; Hüzeir, V; Stam, H; Mertens, F W; van Domburg, R T; Bax, J J; Poldermans, D
Abstract : Background: Chronic obstructive pulmonary disease (COPD) is associated with an increased risk of lung cancer, independently of smoking. However, the relationship between COPD and total cancer mortality is less certain. A study was undertaken to investigate the association between COPD and total cancer mortality and to determine whether the use of statins, which have been associated with cancer risk in other settings, modified this relationship. Methods: The study included 3371 patients with peripheral arterial disease who underwent vascular surgery between 1990 and 2006; 1310 (39%) had COPD and the rest did not. The primary end point was cancer mortality (lung and extrapulmonary) over a median follow-up of 5 years. Results: COPD was associated with an increased risk of both lung cancer mortality (hazard ratio (HR) 2.06; 95% CI 1.32 to 3.20) and extrapulmonary cancer mortality (HR 1.43; 95% CI 1.06 to 1.94). The excess risk was mostly driven by patients with moderate and severe COPD. There was a trend towards a lower risk of cancer mortality among patients with COPD who used statins compared with patients with COPD who did not use statins (HR 0.57; 95% CI 0.32 to 1.01). Interestingly, the risk of extrapulmonary cancer mortality was lower among statin users with COPD (HR 0.49; 95% CI 0.24 to 0.99). Conclusions: COPD was associated with increased lung and extrapulmonary cancer mortality in this large cohort of patients with peripheral arterial disease undergoing vascular surgery. The risk of lung cancer mortality increased with progression of COPD. Statins were associated with a reduced risk of extrapulmonary cancer mortality in patients with COPD.